Impact of Green Marketing And Total Quality Management (TQM) Dimensions on Improving the Financial Performance of Indonesian Sharia Banks: New Concept - Pranata, Sudadi; Narimawati, Umi; Syafei, M. Yani (Journal of Ecohumanism, 2025)
Green marketing is an advertising technique that focuses on promoting and selling products or services that have minimal or positive environmental effect. Given the growing awareness of environmental and sustainability concerns, this concept has gained increasing importance and attention in the fields of marketing and business management. Quality management is a strategy for continuously enhancing (continuous performance improvement) performance at all levels of an organization’s operations and processes, as well as in all functional areas, by leveraging its people and financial resources. How to implement green marketing and total quality management to the financial performance of Bank Syariah Indonesia is the focus of this study. This study aims to investigate the effects of ecological marketing and total quality management on financial performance. This method of research employs multiple linear regression with a sample of 237 individuals, including financial administrators and employees. Consumer awareness has a positive effect on financial performance, consumer loyalty has a positive effect on financial performance, increased resource efficiency has a positive effect on financial performance, an obsession with quality has a positive effect on financial performance, teamwork has a positive effect on financial performance, and engagement and empowerment have a positive effect on financial performance, according to the findings of this study.